The Education of a Circus Clown Mentors, Audiences, Mistakes - Carlyon, David; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
2017 Freedley Award Finalist, Theatre Library Association 2016 Best Circus Book of the Year, Stuart Thayer Prize, Circus Historical Society The 1960s American hippie-clown boom fostered many creative impulses, including neo-vaudeville and Ringling's Clown College. However, the origin of that impulse, clowning with a circus, has largely gone unexamined. David Carlyon, through an autoethnographic examination of his own experiences in clowning, offers a close reading of the education of a professional circus clown, woven through an eye-opening, sometimes funny, occasionally poignant look at circus life. Layering critical reflections of personal experience with connections to wider scholarship, Carlyon focuses on the work of clowning while interrogating what clowns actually do, rather than using them as stand-ins for conceptual ideas or as sentimental figures.
Keywords: Performing arts; Ethnography; Theater-History.